Brand Image, and Food Quality on Purchase Decisions in Meat Processing Industry Products, Canned Food, and Bakery: Brand Image, dan Food Quality Terhadap Keputusan Pembelian pada Produk Industri Pengolahan Daging, Makanan Kaleng, dan Bakery - Lestari, Indah; Sukmono, Rita Ambarwati (Universitas Muhammadiyah Sidoarjo, 2023)
This research aims to determine the influence of Brand image, and Food Quality on Purchasing Decisions on Bernardi Frozen Food Products in Sidoarjo.The sample used amounted to 100 respondents. Samples are taken by the Acidental sampling method. The data analysis technique used is PLS-SEM analysis with the SmartPLS 3.0 program. The results of this study show that Brand image affects Purchasing Decisions, Food Quality affects Bernardi product Purchase Decisions in Sidoarjo.